Sustainable measures for the protection and restoration of soil biodiversity in Germany - Nicole Scheunemann; Luise Xiaqian Doms-Grimm; Christian Ristok; Ricarda Lehmitz (Soil Organisms)
Soils are habitat for the majority of terrestrial life and soil biodiversity plays a crucial role in providing important ecosystem services. However, soil biodiversity is under threat and measures need to be taken to protect and restore it, but conservation so far usually focuses on the protection of attractive or endangered aboveground species. Furthermore, the small size of soil organisms and the considerable taxonomic expertise required for their identification result in a poor consideration of soil biodiversity when evaluating conservation measures. In this review, we compile the available knowledge on the effectiveness of conservation and restoration measures for soil biodiversity in Germany. We provide information on the following habitats: forests, inland wetlands (peatlands and floodplains), coastal sites, and urban areas; and on aboveground as well as belowground soil micro-, meso-, and macrofauna, as well as (to a lesser extent) soil microorganisms. Repeated measures, like management of forest sites are mainly applied in economically utilized areas, with soil biodiversity benefitting from reduced land-use intensity and the creation of a more natural environment. In strongly degraded landscapes (e.g., dried wetlands), an initial impulse measure is usually needed to restore natural conditions, with subsequent conservation management afterwards. In general, habitat heterogeneity is an important factor for increasing soil biodiversity not only above- but also belowground. Its positive effects apply at landscape scale by providing diverse environmental conditions and stepstone habitats, as well as at the small scale with many microhabitats at a few square meters. The main goal of protection and restoration measures must not be to maximize the number of species in a given area, but to establish a habitat-specific species community.